Enzymatic cleavage of model lignin dimers depends on pH, enzyme, and bond type - Jenny R. Onley; Kshitiz Gupta; Markus de Raad; Benjamin P. Bowen; Stephen Tan; Sam Yoder; Kenneth L. Sale; Anup K. Singh; Blake A. Simmons; Paul D. Adams; Trent R. Northen; Kai Deng (Scientific Reports)
Abstract Lignin is composed of phenylpropanoid monomers linked by ether and carbon-carbon bonds to form a complex heterogeneous structure. Bond-specific studies of lignin-modifying enzymes (LMEs; e.g., laccases and peroxidases) are limited by the polymerization of model lignin substrates and repolymerization of cleavage products. Here we present a high throughput platform to screen LME activities on four tagged model lignin compounds that represent the β-O-4’, β-β’, 5–5’, and 4-O-5’ linkages in lignin. We utilized nanostructure-initiator mass spectrometry (NIMS) and model lignin compounds with tags containing perfluorinated and cationic moieties, which effectively limit polymerization and condensation of the substrates and their degrading products. Sub-microliter sample droplets were printed on the NIMS chip with a novel robotics method. This rapid platform enabled characterization of LMEs across a range of pH 3–10 and relative quantification of modified (typically oxidized), cleaved, and polymerized products. All tested enzymes oxidized the four substrates and cleaved the β-O-4’ and β-β’ substrates to monomeric products. We discovered that the active pH range depended on both the substrate and the enzyme type. This has important applications for biomass conversion to biofuels and bioproducts, where the relative percentages of different bond types in lignin varies depending on feedstock and chemical pretreatment methods.